2021
DOI: 10.1021/acs.nanolett.1c03655
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Assembly of 2D Metal-Pyridylporphyrinic Framework Films for Giant Nonlinear Optical Limiting

Abstract: The development of metal–organic frameworks (MOFs) with nonlinear optical (NLO) properties is of pronounced significance for optical devices. Herein, a series of 2D MOFs ZnTPyP­(M) (TPyP = 5,10,15,20-tetrakis­(4-pyridyl)­porphyrin, M = Cu, Ni, Mn, H2) films with [010]-orientation growth composed of ultrathin nanosheets from a pyridylporphyrinic ligand are first obtained by using a liquid-phase epitaxial (LPE) layer-by-layer (lbl) growth approach. ZnTPyP­(M) films show a giant nonlinear optical limiting (OL) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…The binding energies located at 1022.1 and 1045.2 eV correspond to Zn­(II) 2p 3/2 and 2p 1/2 , respectively. , In the N 1s spectra of ZnTCPP­(M) (M = Zn, Mn, and Fe) thin films, a primary peak at about 398.9 eV was assigned to metal-coordinated nitrogen in porphyrin (Figure d). Two N peaks were found for the ZnTCPP­(H 2 ) thin film at 400.1 and 398.1 eV, corresponding to the pyrrolic nitrogen (−NH−) and iminic nitrogen (CN), ,, respectively, indicating that the porphyrinic core was metallized in ZnTCPP­(M) (M = Zn, Mn, and Fe) films and the porphyrinic core was unmetallized for the ZnTCPP­(H 2 ) film. Scanning electron microscopy (SEM) images in Figure e and Figures S10–S12 revealed that the surface of ZnTCPP­(M) (M = Zn, Mn, Fe, and H 2 ) films was well defined, continuous, and uniform.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding energies located at 1022.1 and 1045.2 eV correspond to Zn­(II) 2p 3/2 and 2p 1/2 , respectively. , In the N 1s spectra of ZnTCPP­(M) (M = Zn, Mn, and Fe) thin films, a primary peak at about 398.9 eV was assigned to metal-coordinated nitrogen in porphyrin (Figure d). Two N peaks were found for the ZnTCPP­(H 2 ) thin film at 400.1 and 398.1 eV, corresponding to the pyrrolic nitrogen (−NH−) and iminic nitrogen (CN), ,, respectively, indicating that the porphyrinic core was metallized in ZnTCPP­(M) (M = Zn, Mn, and Fe) films and the porphyrinic core was unmetallized for the ZnTCPP­(H 2 ) film. Scanning electron microscopy (SEM) images in Figure e and Figures S10–S12 revealed that the surface of ZnTCPP­(M) (M = Zn, Mn, Fe, and H 2 ) films was well defined, continuous, and uniform.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As a special subclass of MOFs, porphyrin-based MOFs have been successfully applied to fabricate photoelectronic devices due to their highly delocalized π-electron system and good electron transfer as well as excellent light harvesting. Moreover, the porphyrin structure can be easily tailored by metal substitution at the core to modify the properties and functionalities, ,, which will provide an effective approach to tuning the photoresponse in MOF-based photodetectors. Nevertheless, it is worth noting that tuning metalloporphyrinic ligands to optimize the photodetection performance of porphyrin-based MOFs has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Especially recently MOFs with π-electronic conjugated systems possess third-order nonlinear optics (NLO), showing potential applications in optical limiting (OL), optical switching, and mode-locked laser systems, etc 23 25 . So far, third-order NLO performances of MOFs have been investigated by adjusting different MOFs structural parameters, including the types of metal chelated ligands 26 , construction of interpenetrated networks 27 , encapsulation of guest species and thickness of MOFs film 23 . However, to expand the practical third-order NLO applications of MOFs, more flexible and direct regulation strategies need to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] In recent years, there have been many reports on MPFs. [23][24][25][26][27] Furthermore, the optical nonlinearity and ultrafast NLO response of MPFs have become a major research focus. Porphyrin molecules with an 18 π-electron conjugated system, as well as its derivatives, are considered to be some of the most promising NLO materials because of their excellent NLO properties and good chemical stability.…”
Section: Introductionmentioning
confidence: 99%